Comparison of oxidative stress markers between single and twin gestations in Dorper ewes during pregnancy, delivery and postpartum - Santarosa, B. P. [UNESP] (2021)
Pregnancy in sheep is a physiological condition characterized by a significant increase in energy demand to ensure adequate foetal growth and development, making them susceptible to oxidative stress. The aim of this study was to analyse the markers of oxidative stress in sheep during pregnancy, parturition and close to peripartum (up to 48 h postpartum), comparing single with twin gestation. Sixty healthy Dorper ewes from 2 to 5 years’ old raised under semi-intensive management were used in this study. Ewes were grouped based on foetal number: Group 1, with single pregnancy (n = 30); Group 2, with a twin pregnancy (n = 30). Blood samples were collected nine times: after artificial insemination (D0, control); at 30 days (D30), 90 days (D90), 120 days (D120), 130 days (D130), and 140 days (D140) of pregnancy; on the day of delivery (DD); at 24 h (PD1) and 48 h (PD2) post-delivery. The concentrations of reduced thiol groups (-SH, P = 0.0155), the enzymatic activities of superoxide dismutase (SOD, P = 0.0009), glutathione peroxidase (GSH-Px, P = 0.0110) and catalase (CAT, P = 0.0001) differed according to fetal number by time. Twin gestation decreased concentration of thiobarbituric acid reactive substances (TBARS; P = 0.0278), and TBARS had differed over time (P < 0.0001), but a fetal number by time interaction was not detected (P = 0.2413). Overall, at peripartum period, there was a higher concentration of SOD and glutathione (-SH and GSH-Px), revealing changes on oxidation and antioxidant activity. TBARS concentration was affected by the number of foetus, considering all experimental periods. In conclusion, as gestation progress, the challenges related to the antioxidant status are more pronounced, especially for twin pregnancy, at the final third of gestation.